Implementasi Kurikulum Pembelajaran Islamic Studies dalam Membentuk Sikap Spiritual Siswa - Nur Mawaddah Islamiyah; Reksiana (Qiro'ah : Jurnal Pendidikan Agama Islam, 2020)
This research aims to determine the process of implementing an "Islamic studies" curriculum in shaping students' spiritual attitudes at the International Islamic Secondary School of Republic of Indonesia (IISS RI). This research method uses a qualitative method that is descriptive of analysis with data collection techniques observation obtained from interviews, and documentation. The researcher found that the implementation of "Islamic studies" curriculum was carried out in two ways, namely through academic programs that emphasized cognitive and affective aspects and non-academic programs which emphasized psychomotor aspects, with the application of "Islamic studies" curriculum to shape students' spiritual attitudes such as obeying Allah swt, being sincere, confident, responsible, diligent in learning, honest, disciplined, and respecting others. In addition, the researcher found that the "Islamic studies" curriculum also had a specific target that had to be fulfilled by the students as a requirement for graduation which was by memorizing the Qur'an juz 29 and 30, memorizing the hadith, memorizing dhikr and prayer and being able to give religious lectures.